Computational Thinking in Junior Classrooms in New Zealand - Jeanette Marie Margaret Irons; Maggie Hartnett (Flexible Learning Association of New Zealand, 2020)
From 2020, the New Zealand technology curriculum will include computational thinking. The new curriculum content is being introduced to students from five-years-old onwards. In preparation for its introduction, online resources have been developed for teachers, including junior teachers (who teach new entrants to year three), that contain progress outcomes, lesson plans, exemplars and assessments. However, it is unclear whether New Zealand junior teachers are sufficiently prepared to teach computational thinking and what factors influence their preparedness to teach the new curriculum. This research explored the experiences of a small group of junior school teachers in the year prior to the official introduction of the technology curriculum. Research findings highlight that factors including professional development, assessment, schoolwide support, and time availability influence the uptake of the computational thinking curriculum by teachers in New Zealand junior classrooms.